In Vitro, In Compost, andÂ In VivoÂ Assessment of Chitosan-Polyethylene Glycol as an Intravaginal Insert for Progesterone Delivery in Sheep - E. Y. Yessa; L. I. T. A. Tumbelaka; I. Wientarsih; M. F. Ulum; B. Purwantara; Amrozi (Tropical Animal Science Journal, 2023)
In estrous synchronization, the hormone progesterone is an important element. Various hormone preparations currently available have limitations, especially those related to environmental impact issues. Various alternatives are being studied, and using biodegradable polymeric materials (chitosan-polyethylene glycol combination) to develop new devices is considered one of the solutions. This contribution aims to design and evaluate intravaginal implants that can release progesterone and be degraded in the body and the environment. Implants are made by melting and molding techniques. In vitro drug release studies using dyes as drug models. Implant degradation studies tested in compost. Changes in the shape of the implant, while it is in the vagina, are observed by ultrasound. Blood collection was performed three days before and during implantation to obtain a blood progesterone profile. In vitro drug release studies using dye as a drug model showed a chitosan-PEG profile that released the drug faster at first, then slowed down. Implant degradation studies in compost and vagina demonstrated a gradual degradation process. The blood progesterone profile increased during implantation, as high as 15 ng/mL on the third day. In conclusion, the chitosan-PEG intravaginal implant formulation designed using the melting and molding technique proved to be degraded in the compost environment. It released the hormone progesterone for four days according to the degradation period of the implant in the vagina.